2022
DOI: 10.1097/spv.0000000000001215
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Promotors to Health Service Utilization for Pelvic Floor Disorders in the United States: Systematic Review and Meta-analysis of Qualitative and Quantitative Studies

Abstract: Importance We need a systematic approach to understanding health service utilization behavior in women with pelvic floor symptoms in the United States.Objectives The aim of this study was to determine the prevalence of pelvic floor care utilization and identify its barriers and promotors using Andersen's model, which theorizes care-seeking behavior with individual care needs, resources, predispositions, and macrostructures. Design This was a systematic search of studies on care-seeking patterns in women with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Reproductive age and married women can get support and access to money compared to their counterparts. A systematic review and meta-analysis conducted on barriers and promoting factors to health service utilization for pelvic floor disorder in the United States showed that having social support and established primary/secondary care were facilitating factors for care seeking [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproductive age and married women can get support and access to money compared to their counterparts. A systematic review and meta-analysis conducted on barriers and promoting factors to health service utilization for pelvic floor disorder in the United States showed that having social support and established primary/secondary care were facilitating factors for care seeking [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from eastern Ethiopia and Iran showed that a moderate wealth index and financial support improved health seeking behavior of women with pelvic floor disorders [ 68 , 69 ]. In addition, lack of awareness about the pelvic floor and experiencing fear were barriers to care-seeking [ 66 , 68 , 69 ]. A systematic review conducted in the United States showed that health service utilization for pelvic floor disorder was low among Black women [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A recent systematic review also found over 60% of women with symptomatic PFDs do not seek care, with even lower utilization rates among younger and minority women. 12 Strategies to address disparities in overall postpartum care have been studied including the use of patient navigators. 5,41 However, to our knowledge, there is no study to date that addresses or inquires about health disparities in postpartum pelvic floor care in the United State.…”
Section: Disparities In Postpartum and Pelvic Floor Carementioning
confidence: 99%
“…11 Several large studies have found significant inequities in rates of care utilization, surgical complications, medication prescription patterns, and the formation of clinical guidelines in historically marginalized populations. [12][13][14][15] However, the understanding of health disparities in postpartum PFD care remains understudied. This needs to be urgently and systematically examined, given the abundance of health disparities found in both postpartum and PFD care.…”
Section: Introductionmentioning
confidence: 99%